The FHA Analysis of Dual-Bridge LLC Type Resonant Converter - Arnold Fredderics; K.Vinoth Kumar; Jeya Selvan Renius; Raja Guru; Sree Lakshmi Nair; K. Viswanatha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
The dual bridge resonant converter is designed in this paper. In this converter the LLC type resonance configuration is proposed .This types is compared with the other configurations and its benefits are narrated in this paper. The steady-state analysis of the LLC configuration is done using fundamental harmonics approximation method and the values for the components of resonance configuration is found and used for simulation. The simulation results shows that the converter is able to achieve the zero voltage switching for the wide load range and attains a good efficiency.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6513